Synthesis, Identification and Biological Activity of New Heterocyclic Compounds from Reaction of New Schiff-Bases with Phathalic Anhydride - Dawood, Alya A.; Mohammed, Shireen R.; Mahmoud, Mohammed (Science Journal of University of Zakho, 2020)
Series of new Schiff bases and their derivatives (Oxazepine) have been synthesized during two steps. The first step synthesis of imines derivatives (1-10) by the condensation reaction of 1, 7-diaminohepatane and 1,8-diaminooctane with different substituted aromatic aldehydes by using glacial acetic acid as catalyst. The second step includes reaction of the prepared Schiff bases derivatives with phathalic anhydride in dry benzene to obtain   seven-membered heterocyclic ring derivatives (11-15).  The biological activities of some prepared compounds were also studied against different kinds of bacteria. The new derivatives were confirmed by suing a range of experimental techniques including 1HNMR, 13C NMR, IR and Mass spectra.
Keywords: Oxazepine; Schiff bases; 1, 7-diaminoheptane; 1, 8-diaminooctane; Antibacterial activity; phathalic anhydride